Family Law Reform in Morocco - Zulham Wahyudani; Jefry Tarantang; Nurrohman Nurrohman; Tatang Astarudin (Hukum Keluarga Islam IAIN LANGSA, 2023)
The research on family law reform in Morocco aims to analyze the changes in family law in Morocco after the reform in 2004. The study discusses child marriage and the impact of the reforms on society, particularly in relation to gender equality and legal protection for women and children. This research is normative-explanatory and explains family law reform in Morocco by using a literature review to analyze policies. The results show that family law reform in Morocco has improved gender equality and provided better legal protection for women and children. However, there are still some challenges in the application of the law, such as changing attitudes towards tradition and culture and difficulties in applying the law in remote areas. This research can contribute to an understanding of the changes in family law in Morocco and can be used as a reference in efforts to improve legal protection for women and children in other countries that have similar legal systems.